OA02.08. Chick embryo model an experimental model for drug discovery in ayurveda. - Tomar, Ekta (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: There has been a continuous and increasing demand for newer experimental models in various studies like Teratogenicity, Pathogenicity, carcinogenicity, mutagenicity, stem cell research, viral studies, in preclinical studies to generate a database for ayurvedic drugs. To serve this purpose Chick Embryo as an experimental model is proposed because of its rapidity, validity Easy handling and availability throughout the year. And as it is an exvivo model, the ethical problems can be lessened. METHOD: The fertilized eggs are cleaned by 70% ethanol and kept in a 370 C humidified incubator. These eggs can now be taken from 0 embryonic development day (EDD) till hatching, depending upon the type of study. To observe the changes after inducing the drug the model can be visually assessed and are photographed for further analysis. The tissues can be excised and taken for histological studies and also the various dyes can be injected to visualize the dynamic changes in the growth patterns. With the aid of sophisticated technique the chick embryo can be taken for shell less studies. RESULT: Hence, it can be concluded that the Chick Embryo model may be one of the best model in recent trends for drug discovery and it can be also used to establish the preclinical parameters for the preexisting Ayurvedic formulations. This is an easy model to validate and generate a data base for ayurvedic drugs. CONCLUSION: Hence, it is proved in a larger extant that chick embryo may be an ideal and It can also be one of the widely preferred model for drug discovery in Ayurvedic research. There is a need of present era to have an scientific data, this model can help our to do so.